Exploring the role of ferroptosis in the doxorubicin-induced chronic cardiotoxicity using a murine model. (25th August 2022) - Li, Xiaofen; Liang, Jiyi; Qu, Liping; Liu, Sili; Qin, Anquan; Liu, Honglin; Wang, Tao; Li, Wei; Zou, Wenjun
Abstract: Doxorubicin (DOX) is an effective antitumor drug; however, but its clinical application is seriously limited by the cardiotoxicity induced by its use. Recent studies have found that ferroptosis is an important mechanism underlying DOX-induced cardiotoxicity. However, existing studies are based on DOX-induced acute or subacute cardiotoxicity model. Therefore, we established a murine model of DOX-induced chronic cardiotoxicity using the clinically relevant cumulative dose, to evaluate the potential molecular mechanism underlying ferroptosis of cardiomycocytes. Male C57 mice were received intraperitoneal injections of DOX at a dose of 3 mg/kg body weight, once a week for 12 weeks. We dynamically analysed echocardiographic findings, serum myocardial enzyme levels, haematological indexes and cardiac histopathological changes. The results showed that, after receiving a cumulative DOX dose of 15 mg/kg, the mice developed anaemia and the function and structure of the heart changed significantly with an increase in the cumulative DOX dose. Importantly, with a cumulative DOX dose of 36 mg/kg, iron overload occurred in the heart tissue. Moreover, RNA-sequencing analysis and experimental verification revealed that ferropotosis is the underlying mechanism of DOX-induced chronic cardiotoxicity. Our results showed that DOX inhibits Slc7a11 in system-Xc, resulting in the reduction of GSH synthesis to prevent GPX4 from scavenging lipid peroxides. In addition, DOX induced the occurrence of ferroptosis via down-regulating Nrf2 expression to inhibit HO-1 and GPx4 levels. Our study provides a new perspective for evaluating the pathophysiology of DOX-induced chronic cardiotoxicity in the future, and developing new potential therapeutic strategies for the prevention and treatment of DOX-induced cardiotoxicity. Graphical abstract: Image 1 Highlights: Chronic cardiotoxicity is most common type of doxorubicin cardiotoxicity. Ferropotosis is underlying mechanism of doxorubicin chronic cardiotoxicity. Xc-/GPx4 and Nrf2/HO-1 is main pathway of ferroptosis.